5 – 6 gadus vecu bērnu saskarsmes prasmju veicināšana rotaļnodarbībās - Strazdiņa, Madara (Latvijas Universitāte, 2015)
„5 – 6 gadus vecu bērnu saskarsmes prasmju veicināšana rotaļnodarbībās” Darba autore: Madara Strazdiņa Zinātniskā vadītāja: Mg.paed., Mg.phil. lektore Ērika Lanka Diplomdarba apjoms: 46 lpp., 6 tabulas, 11 attēli, 3 pielikumi, izmantoti 38 literatūras avoti. Darba aktualitāte balstās uz problēmu, kā veicināt 5 – 6 gadus vecu bērnu saskarsmes prasmes rotaļnodarbībās. Darbā ir raksturots saskarsmes jēdziens un rotaļspēles būtība un nozīme bērna saskarmes prasmju atīstībā dažādu autoru skatījumā. Darbā tika veikts praktiskais pētījums Rīgas pirmsskolas izglītības iestādē X par saskarsmes prasmju veicināšanas iespējām rotaļnodarbībās 5 – 6 gadus veciem bērniem. Diplomdarba ietvaros tika analizēta teorētiskā literatūra, veikti secinājumi un piedāvāti ieteikumi.

„Stimulation of interpersonal communication skills of 5-6 years old children during playing activities”. The author of the diploma work: Madara Strazdina The scientific leader: Mg.paed., Mg.phil. lecturer Erika Lanka The volume of the diploma work: The topicality of the diploma work is the issue of stimulation of interpersonal communication skills of 5-6 years old children during playing activities. The diploma work describes the concept of interpersonal communication as well as the essence of the playing activity itself and the importance of the development of interpersonal communication skills of children from the views of various authors. A practical study was carried out within the framework of the diploma work at Riga preschool educational institution X on the opportunities of stimulation of interpersonal communication skills of 5-6 years old children during playing activities. The analysis of theoretical literature as well as conclusions and further recommendations were given in the framework of the diploma work.
Stimulation of Interpersonal Communication Skills of 5-6 Years Old Children During Playing Activities
Keywords: Pedagoģija; saskarsme; saskarsmes prasmes; rotaļspēle; sadarbība; pedagogs